Carbon Capture From Flue Gas and the Atmosphere: A Perspective - Wang, Xiaoxing; Song, Chunshan (Frontiers in Energy Research, 2020)
Climate change has become a worldwide concern with the rapid rise of the atmospheric Co2 concentration. To mitigate Co2 emissions, the research and development efforts in Co2 capture and separation both from the stationary sources with high Co2 concentrations (e.g., coal-fired power plant flue gas) and directly from the atmosphere have grown significantly. Much progress has been achieved, especially within the last twenty years. In this perspective, we first briefly review the current status of carbon capture technologies including absorption, adsorption, membrane, biological capture, and cryogenic separation, and compare their advantages and disadvantages. Then, we focus mainly on the recent advances in the absorption, adsorption, and membrane technologies. Even though numerous optimizations in materials and processes have been pursued, implementing a single separation process is still quite energy-intensive or costly. To address the challenges, we provide our perspectives on future directions of Co2 capture research and development, that is, the combination of flue gas recycling and hybrid capture system, and one-step integrated Co2 capture and conversion system, as they have the potential to overcome the technical bottlenecks of single capture technologies, offering significant improvement in energy efficiency and cost-effectiveness.